Investigation leading to a process for the synthesis of hydrogen sulphide from sulphur and certain lubricating oils derived from petroleum - Schauder, H (Rhodes University, Faculty of Science, Department of Chemistry, 1952)
The primary object of the present study was to provide a process adaptable to prevailing South African conditions, for the manufacture of hydrogen sulphide. Such a process would also be suitable for use in other countries where the gas is not obtainable naturally or from refinery operations or as a by-product from other industries. Early in the study it was found that the literature embodying prior work was very scattered in character and had to be sought in many different fields of research. It was therefore decided to make the record of prior work as comprehensive as possible so as to provide, at the same time, a starting point tor future workers on related subjects. Intro., p. 1.
Keywords: Hydrogen sulfide